Efeitos do estresse por separação maternal em micróglias de camundongos machos e fêmeas - Laila Blanc Árabe (2021)
Early life stress modifies behavior and function aspects of brain in long term. It is related to several psychiatric disorders, such as depression and anxiety disorder, schizophrenia and drug abuse. Symptoms start in adolescence and patients present alterations in the neurodevelopment before this period. It is crucial to unveiling cellular and molecular modifications in response to early life stress in windows of vulnerability prior to adolescence in order to better understand the pathogeny of such disorders – thus, to better psychiatric outcomes. The neurodevelopment relies on a healthy microenvironment, with major participation of glia cells, such as microglia cells. It is possible that endogenous or exogenous disturbance of this immune cells leads to erroneous development of neural circuits and increased susceptibility to stress. Importantly, the inclusion of female animal models is urgent, once sexual dimorphism is observed in the incidence and symptomatology of neurodevelopmental disorders and in microglia function. We hypothesize that post-natal stress modifies the density and morphology of microglia in short and long term, but in a sex-dependent manner. To test this hypothesis, we used a 13-days maternal separation protocol on CXCR1 GFP/+ transgenic mice and inquired microglia density and morphology in ventral hippocampus at post-natal day 15 and 30 (P15 and P30). Only females responded to early life stress. At short term (P15) microglia decreased their complexity and cell size, presenting a transition/de-ramified-like morphology – which persisted at P30. Interesting, this morphology is similar to male microglia morphology in both ages. We also reported sex differences in females in the developmental dynamics between P15 and P30 – in which females presented a surveillant-like microglia morphology at P30, while males did not differ their morphology. On the other hand, males had increased density of microglia in hippocampus at P15. Our work indicates microglia as a cell of interest to studies of early life stress, mainly in females. These results highlight the importance of inclusion of female models on microglia and early life stress studies. Finally, we encourage more detailed studies to unveil the functional consequences of the presented results.